Innovations in Separations Technology for the Recycling of Rare Metals with Supercritical Carbon Dioxide - M. Faisal (Syiah Kuala University, 2012)
This study deals with the utilizing of supercritical CO2 for recycling of rare metals(i.e. Pt, Pd, Rh) from spent materials. Experiments were conducted at the temperature range of 40-60°C and a pressure up to 30 MPa. A variety of ligands such as tributyl phosphate and acetyl acetone were introduced. The mechanism of complex formation of chelating ligand and rare metals in supercritical CO2 was presented. It has been observed that the extraction efficiency of rare metals was strongly dependent on temperature, pressure and the nature of the ligand